Pie sharing and pie expansion in buyer-supplier new product development partnerships. (14th February 2020) - Wölfel, Joachim; Grosse-Ruyken, Pan Theo
Firms seek new product development (NPD) partnerships to achieve competitive advantage by pooling interorganisational resources. Although such collaborations may expand the partnership's total value pie, sharing the pie often results in poisonous win-lose rivalry amongst partners. This study investigates how automotive suppliers may gain competitive advantage and increase their financial stake within NPD partnerships with OEMs. We analyse sources of pie expansion from a resource-based view (RBV) perspective and the mediating role of fairness in pie sharing. As NPD partnerships also induce dependencies between collaborating firms, we extend the RBV with arguments from resource dependence theory (RDT). We test our predictions on a sample of 147 NPD partnerships between tier-1 suppliers and OEMs. Our findings suggest that fairness in pie sharing significantly mediates pie expansion. Moreover, NPD partnerships enable suppliers to increase OEMs' dependency on their firm, which mediates suppliers' competitive advantage, resulting in a more equitable division of the value pie.